2016
DOI: 10.1007/s00702-016-1578-6
|View full text |Cite
|
Sign up to set email alerts
|

A53T in a parkinsonian family: a clinical update of the SNCA phenotypes

Abstract: Approximately 15 % of PD patients with Parkinson Disease (PD) have the familial type and 5-10 % of these are known to have monogenic forms with either an autosomal dominant or a recessive inheritance pattern. Here, we report on a family carrying the A53T SNCA mutation and we review SNCA mutation phenotypes by comparing point mutations within each other as well as with duplication and triplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…The frequency of anxiety (Tc 3.4%, Dc 5.0%, and PMc 5.9%) and sleep disturbances (Tc 20.7%, Dc 17.3%, and PMc 10.3%), usually presenting as RBD, manifest with a similar frequency for all 3 groups (Tambasco et al, 2016). Also, 69% of Tc, 42.5% Dc, and 25% of PMc have cognitive impairment (Tambasco et al, 2016). Furthermore, psychosis is more frequent among patients with Tc (69.0%) than those with either Dc (40%) or PMc (7.3%) (Tambasco et al, 2016).…”
Section: Park1/park4-sncamentioning
confidence: 94%
See 3 more Smart Citations
“…The frequency of anxiety (Tc 3.4%, Dc 5.0%, and PMc 5.9%) and sleep disturbances (Tc 20.7%, Dc 17.3%, and PMc 10.3%), usually presenting as RBD, manifest with a similar frequency for all 3 groups (Tambasco et al, 2016). Also, 69% of Tc, 42.5% Dc, and 25% of PMc have cognitive impairment (Tambasco et al, 2016). Furthermore, psychosis is more frequent among patients with Tc (69.0%) than those with either Dc (40%) or PMc (7.3%) (Tambasco et al, 2016).…”
Section: Park1/park4-sncamentioning
confidence: 94%
“…They found that among the reported 137 cases, depression is more common in Tc (69.0%) and Dc (35.0%) than in PMc (13.2%) (Tambasco et al, 2016). The frequency of anxiety (Tc 3.4%, Dc 5.0%, and PMc 5.9%) and sleep disturbances (Tc 20.7%, Dc 17.3%, and PMc 10.3%), usually presenting as RBD, manifest with a similar frequency for all 3 groups (Tambasco et al, 2016). Also, 69% of Tc, 42.5% Dc, and 25% of PMc have cognitive impairment (Tambasco et al, 2016).…”
Section: Park1/park4-sncamentioning
confidence: 99%
See 2 more Smart Citations
“…Parkinson's disease(PD) is the second most common neurodegenerative disease after Alzheimer's disease (AD) [2].Although genetic, environmental and aging factors play a role in the pathogenesis of PD, the exact pathogenesis is not clear [3,4].Two important neuropathological features of PD are characterized by specific iron accumulation in the substantia nigra and residual eosinophilic inclusions in dopamine neurons, which is the Lewy body [5].Because of the cytotoxic effect of iron and its ability to promote the production of oxygen free radicals, the role of iron in PD cannot be ignored [6][7][8].A large number of studies have confirmed that black matter iron accumulation is involved in the pathogenesis of PD. Iron-selective deposition has been found in the substantia nigra of PD patients and animal models [9]In the present study, SH-SY5Y dopaminergic cells were treated with iron to explore theregulationofRab protein associated with exosomes.…”
Section: Introductionmentioning
confidence: 99%